Tunisian Fragile Democratization: Case of Democratic Backsliding during Kais Saied’s Presidency - Ajeng Nadiya Husna Syahba; Adhi Cahya Fahadayna (Journal of Law, Politic and Humanities, 2024)
Tunisia is the only Arab country that has successfully carried out a revolution and democratization after the Arab Spring. However, this success cannot guarantee that democracy can survive and run well, especially in meeting the demands or expectations of the community. This paper aims to explain the decline of democracy during the Kais Saied administration after ten years of democracy implemented in Tunisia. This research uses Quantitative methods to explain the obstacles to the development of democracy. Multiple regression analysis techniques were used in this research to analyze the primary data: the Democracy Index by the Economic Intelligence Unit, Tunisia's GDP Growth (Annual) by the World Bank, and the Freedom of the World score by Freedom House to determine the influence of economic growth and the level of freedom on the decline of democracy in Tunisia. The study results show that economic growth and the level of freedom are interrelated with the prevailing government system. Aspects of political culture among the community and political elites influence the implementation of democracy. Democracy has not been able to be the key to overcoming challenges related to economic growth and high levels of corruption in Tunisia. The failure of political parties to carry out their duties and establish good relations with the community has hampered the development of democracy and encouraged the decline of the democratic regime in Tunisia through President Kais Saied's decision to dissolve parliament.